Severity of sleep apnea impairs adipose tissue insulin sensitivity in individuals with obesity and newly diagnosed obstructive sleep apnea - Rodrigues, Sara; Bortolotto, Luiz Aparecido; Beyl, Robbie A.; Singh, Prachi (Frontiers in Sleep, 2023)
Introduction Obstructive sleep apnea (OSA) is a common sleep disorder associated with increased risk for the development of type 2 diabetes. While studies have examined the effects of sleep on whole-body insulin sensitivity, little is known about the effects of sleep on adipose tissue insulin sensitivity in patients with OSA. We analyzed if the severity of OSA, measured by apnea-hypopnea index (AHI), is associated with adipose tissue insulin sensitivity. Methods We examined the relationship between sleep parameters and adipose tissue insulin sensitivity in non-diabetic participants with obesity and newly diagnosed OSA who underwent overnight polysomnography and a 2 h oral glucose tolerance test during which circulating free fatty acids were measured. In total, 16 non-diabetic participants with obesity and newly diagnosed OSA (sex, 81.3% males; mean age, 50.9 ± 6.7 y; BMI, 36.5 ± 2.9 kg/m2; AHI, 43 ± 20 events/h) were included in the analysis. Results In our study participants, AHI is inversely associated with free-fatty acid suppression during oral glucose challenge (R = −0.764, p = 0.001). This relationship persisted even after statistical adjustment for age (R = −0.769, p = 0.001), body mass index (R = −0.733, p = 0.002), waist-to-hip ratio (R = −0.741, p = 0.004), or percent body fat mass (R = −0.0529, p = 0.041). Furthermore, whole-body insulin sensitivity as determined by the Matsuda index was associated with percent REM sleep (R = 0.552, p = 0.027) but not AHI (R = −0.119, p = 0.660). Conclusion In non-diabetic patients with OSA, the severity of sleep apnea is associated with adipose tissue insulin sensitivity but not whole-body insulin sensitivity. The impairments in adipose tissue insulin sensitivity may contribute to the development of type 2 diabetes.